Accessibility and Development in Peripheral Regions. The Case for Beira Interior - Jorge Miguel Reis Silva (European Regional Science Association (ERSA), 2006)
Beira Interior is a Portuguese region located at the centre of Portugal, close to the Spanish border, and traditionally seen as a strongly peripheral region. In the last years the decrease in population and weaknesses of the industrial park have been justified on basis of shortness and/or lack of quality in transport infrastructure. In order to evaluate whether there is in fact a case in favour of infrastructure shortage we have developed a methodology that would allow us to identify the accessibility gains in the recent past, the ones foreseeable in the usually adopted planning periods and the ones possible in a asymptotic scenario of strong generalised accessibility, enabling this way to make explicit identification of the gains already achieved and the ones still possible. The evolution of values of the studied region was compared with the corresponding values in the region Litoral Centro – the region that was also used as benchmark in a previous consultation process to industrial key informants operating in Beira Interior. This thematic is extremely important for the region and for the country since the conclusions obtained will enable a better supported discussion on additional investment in transport infrastructure.
Keywords: 330